Variable Volumes of Resected Bone Resulting From Different Total Ankle Arthroplasty Systems. (August 2016) - Goetz, Jessica E.; Rungprai, Chamnanni; Tennant, Joshua N.; Huber, Emmalei; Uribe, Bastian; Femino, John; Phisitkul, Phinit; Amendola, Annunziato
Background: The increased popularity and success of total ankle arthroplasty (TAA) has resulted in the development of varying TAA hardware designs, many of which include specific bone-sparing or bone-sacrificing features. The goal of this work was to determine differences in the volume of bone removed for implantation of different total ankle arthroplasty hardware systems. Methods: Sixteen cadaveric specimens were computed tomography–scanned preoperatively and after total ankle arthroplasty using either an INBONE II, Salto Talaris, STAR, or Zimmer TMTA implant. Geometries of the talus and the distal tibia were manually segmented and converted to 3D bony surface models. The volume of bone removed for each implant was calculated as the difference in volume between the preoperative and postoperative bone models. To account for differences in specimen size, volume was expressed as a percentage of the intact bone. Results: There was a significant difference ( P = .049) in the average percent of talar bone removed, with the STAR and INBONE II systems requiring removal of greater volumes of bone. The INBONE II system required significantly ( P < .004) more tibial bone resection than the other 3 implants when evaluating a long span of the distal tibia. However, most of this increased bone resection was medullary bone. Close to the articular surface, bone volumes removed for the various tibial components were not significantly different ( P = .056). Conclusion: Volume and location of bone removed for different implant systems varied with implant design. Clinical Relevance: Primary bone resection associated with different implant hardware systems varied more on the talar side of the articulation, and the stemmed prosthesis did not result in dramatic increases in periarticular bone resection. Clinicians should weigh the effects of greater or lesser bone resection associated with various implant designs against other factors used for hardware selection.